A methionine/aspartate-rich synthetic peptide delineated from N-terminal region of nucleophosmin protein effectively protects against cadmium-induced toxicity - Yan, Rui; Tan, Heng Wee; Zhao, Xiao-Yun; Wu, Jia-Yi; Zhong, Qiu-Hua; Wang, Xiu-Yun; Cai, Na-Li; Xu, Yan-Ming; Lau, Andy T.Y. (Environment international, 2025)
[Display omitted] •NPM1 is a novel Cd-binding protein.•Cd binds to the M/D-rich region (MEDSMDMDM) of NPM1 and triggers nucleolar stress.•Cd induces nucleoplasmic translocation of NPM1 and inhibits rRNA biogenesis.•Synthetic M/D-rich peptide mitigates Cd toxicity in cells and at animal levels. Cadmium (Cd) is a widespread toxic heavy metal, and exposure to Cd is a growing environmental health concern. The molecular mechanism of Cd cytotoxicity is complicated and still not well understood, and treatment options for Cd cytotoxicity are lacking. Currently, only a limited number of Cd-targeted proteins have been identified. Here, we used Cd-immobilized metal ion affinity chromatography (Cd-IMAC) coupled with LC-MS/MS technique to detect putative Cd-binding proteins in human cells, and nucleophosmin (NPM1) was identified as the top Cd-binding protein. We found that Cd bound exclusively to the methionine/aspartate (M/D)-rich region (MEDSMDMDM) of NPM1, and NPM1 was essential for Cd-induced apoptosis. Furthermore, Cd could trigger intracellular nucleolar stress by causing nucleoplasmic translocation of NPM1 and decreasing pre-rRNA levels through binding to the M/D-rich region of NPM1. Interestingly, we discovered that a short peptide containing only the M/D-rich region of NPM1 could effectively mitigate Cd toxicity, both in vitro and in vivo. Specifically, the synthetic M/D-rich peptide demonstrated significant protection against Cd toxicity, particularly in the liver. It significantly reduced Cd concentration, suppressed the upregulation of blood ALT and AST levels, and alleviated liver inflammation in Cd-exposed BALB/c mice. This study reveals a novel mechanism of Cd cytotoxicity through NPM1-regulated nucleolar stress and apoptosis. Additionally, it identifies a short peptide with strong clinical potential to counteract Cd toxicity.